Outdoor thermal comfort index in Malaysian urban areas - Hanipah, Mohd Hafizal (2019)
Rapid urbanisation and industrialisation have adversely impacted the urban environmental heat stress due to urban heat island phenomenon. These thermal environmental problems can be even more challenging to people living in urban areas with tropical hot and humid climatic conditions throughout the year. Buildings in urban area is one of the major elements that contributes to the heat stress problem. The objectives of the study are threefolds. First, to evaluate outdoor thermal comfort by using Universal Thermal Climate Index (UTCI) associated with regression equation during the hottest daily temperature based on 3 years of hourly climatic data at principal meteorological stations of five selected cities in Malaysia. Second, to simulate the current urban layout of the five cities with different types of area (i.e., residential, commercial and industrial areas) based on the analysed climatic input data of the worst case scenario by using Computational Fluid Dynamic (CFD) modelling to investigate its impact on UTCI. Third, to establish the most influential building arrangement parameter towards the outdoor thermal comfort. It was revealed that the UTCI values at five principal meteorological stations for the worst case scenario of heat stress were in the range of 35 °C to 37 °C. Meanwhile, the predicted UTCI levels due to the impact of buildings within the current urban layouts of the five cities were generally higher in the range of 39 °C to 47 °C. Alor Setar’s residential area was found to have the lowest UTCI while Alor Setar’s industrial area demonstrated the highest UTCI value. The predicted results from the Pearson coefficient correlation analysis revealed that packing density and H/W ratio are the two parameters that show significant impact toward UTCI with the correlation coefficient (R2) of 0.746 and 0.689 respectively. However, the result from MLR analysis showed that packing density is the one and only BAP that has strong positive influence towards UTCI with the correlation coefficient (R2) of 0.557.